(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
As technology continues to advance, there is a growing interest in personalized customization with diverse styles and a high degree of fit. To address challenges such as long production cycles and high labor and material costs associated with personalized customization, there has been significant research on automatic pattern generation. However, most of these studies focus on relatively single garment styles. Therefore, this paper proposes a method for automatically generating multi-style collar patterns. First, by analyzing the characteristics of stand collar styles, the modules of stand collar are determined, and the control attributes and methods of each module are determined according to the actual needs. Based on this, a modular design method for stand collar is constructed; the neck parameters and stand collar structure are statistically analyzed, and a mapping model between neck parameters and stand collar structure is established; then, the relationship between stand collar modules and paper patterns is analyzed, and a relationship model between numerical control modules and paper pattern parameters is established to achieve the purpose of driving stand collar structure parameters by stand collar styles; then, according to the stand collar structure design method, the key points of the pattern are parameterized, thus realizing the parametric design of the stand collar pattern; finally, using Matlab software, different components are coordinated, and the modular design method and parametric design of stand collar are comprehensively applied to realize the automatic generation of different styles of stand collar patterns. The research shows that the automatic pattern generation method established in this paper can meet the automatic pattern generation of different stand collar styles, and reduce some human and material costs for the pattern making process in the clothing industry.